2003
DOI: 10.1897/02-183
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and chemistry of aspen wood leachate to aquatic life: Field study

Abstract: A dark, toxic leachate has been observed around woodpiles of trembling aspen (Populus tremuloides Michx.) cut in winter for pulp or structural lumber. We measured production of leachate from 18 m3 of harvestable aspen logs stacked in an open field near Dawson Creek, British Columbia, Canada. The logpile began producing leachate during the first winter thaw and continued to do so for the duration of the two-year study (mean, 250 L/collection). Aspen leachate was characterized by dark color, acidic pH (5.0-6.5),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…COD values did not change significantly after 24 and 72 h of leaching procedure, ranging from 622 to 1411 mg O 2 /L at 24 h, and from 954 to 1452 mg O 2 /L at 72 h. For both tropical and native species, COD was up to six times lower than wood leachate COD produced from Populos tremuloides Michx. [20], but similar to that found on leachates obtained from woody wastes [10]. Salinity levels were in the best range of 33-35‰.…”
Section: Physico-chemical Parameterssupporting
confidence: 82%
“…COD values did not change significantly after 24 and 72 h of leaching procedure, ranging from 622 to 1411 mg O 2 /L at 24 h, and from 954 to 1452 mg O 2 /L at 72 h. For both tropical and native species, COD was up to six times lower than wood leachate COD produced from Populos tremuloides Michx. [20], but similar to that found on leachates obtained from woody wastes [10]. Salinity levels were in the best range of 33-35‰.…”
Section: Physico-chemical Parameterssupporting
confidence: 82%
“…Higher surface area to volume ratio of the smaller chips contributed to greater COD at Muldowan 22 [27]. Elevated COD levels are associated with increased toxicity as shown by previous work with aspen leachate [7,23], pulp mill effluent [28,29] and municipal landfill leachates [28,30]. True color also differed between sites, with the smaller chips from Muldowan 22 producing more highly colored leachate than the larger chips from Muldowan 18 (Mann-Whitney U = 1.00, p = 0.001) Although there were no significant difference in phenols between samples, there was an increase in phenols at both sites during the first spring sampling followed by a decreased over the remaining sampling period.…”
Section: Operational Samplesmentioning
confidence: 56%
“…Accordingly, it is reasonable to suggest that residual chip piles can produce toxic leachate for close to two years following biomass operations, if not longer. Similarly, Taylor and Carmichael [7] noted that an 18-m 3 aspen log pile produced toxic leachate after two years and that only 10% of leachable material had been removed from the pile over the two-year exposure period. Although our piles consisted of chips not logs, and conifers not angioperms, and were considerably smaller at approximately 0.33 m 3 , our findings agree with others and indicate the potential for leachate generation where wood chip or log piles exist.…”
Section: Operational Samplesmentioning
confidence: 89%
See 1 more Smart Citation
“…Those authors observed that higher toxic effects on the early stages of the runoff were gradually reduced, and that 90% of toxic effects were associated with the first 20% of the total runoff volume. Even though the toxic effects posed by wood-related compounds have been demonstrated [9,10,11,6,4], little is know concerning the intra-storm magnitude, variability and possible existence of toxic first flushes from stormwater runoff generated in log-yards. The aim of this paper was to evaluate the magnitude and the intra-storm variability of the toxic effects posed by stormwater runoff originated from a log-yard during single storm events.…”
Section: Introductionmentioning
confidence: 99%